Pengembangan Model Pembelajaran Speaking Bahasa Inggris Berbasis Kearifan Loka - Deni Dzulfaqori Nasrullah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2018)
In this global era, English has the significance effect to the school,politic, and culture. For the English teachers need to make sure thatthey can give the contribution to English education in this country.The teachers need to realize that teaching English is not onlytransferring four basic skills, that is reading, writing, listening, andspeaking, to the students, but the teachers need to apply the localwisdom concept. Through the model of teaching English speakingbased on local wisdom, it makes the new model of teaching and doesnot only focus on English itself. Qualitatively, this researchdescribes the model of conceptual teaching English Speaking basedon local wisdom. So that, it is known that teaching English based onlocal wisdom can be developed more various. In this time through themodel of talking riddle (tatarucingan) and words games (kaulinan).